2018
DOI: 10.3390/molecules23050994
|View full text |Cite
|
Sign up to set email alerts
|

To Decipher the Mycoplasma hominis Proteins Targeting into the Endoplasmic Reticulum and Their Implications in Prostate Cancer Etiology Using Next-Generation Sequencing Data

Abstract: Cancer was initially considered a genetic disease. However, recent studies have revealed the connection between bacterial infections and growth of different types of cancer. The enteroinvasive strain of Mycoplasma hominis alters the normal behavior of host cells that may result in the growth of prostate cancer. The role of M. hominis in the growth and development of prostate cancer still remains unclear. The infection may regulate several factors that influence prostate cancer growth in susceptible individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 52 publications
0
14
0
1
Order By: Relevance
“…The concentration of the free drug was calculated from the calibration curve of NF. The percentage of loading was calculated using the following eqn (1) Loading% ¼ mass of drug immobilized on carrier mass of carrier loaded with drug  100 (1)…”
Section: Loading Of Nf Into Nanocarriersmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration of the free drug was calculated from the calibration curve of NF. The percentage of loading was calculated using the following eqn (1) Loading% ¼ mass of drug immobilized on carrier mass of carrier loaded with drug  100 (1)…”
Section: Loading Of Nf Into Nanocarriersmentioning
confidence: 99%
“…Thus, the intercellular infection of M. hominis in host cells may assist as a potential issue in prostate cancer etiology. 1 Hyperthermia therapy is a type of medical treatment in which the body tissue is exposed to a higher temperature (up to 45 C) to treat and destroy cancer cells or shrink tumors. The damage to cells during hyperthermia can make them more sensitive to the effects of chemotherapy and radiation therapy so these treatments work better.…”
Section: Introductionmentioning
confidence: 99%
“…The association of infectious agents in the etiology of different types of cancer has piqued the interest of scientists in recent years. Recent data have shown the involvement of Mycoplasma hominis, Chlamydia pneumoniae, and Escherichia coli infection in the etiology of prostate cancer, lung cancer, and colon cancer, respectively [9][10][11][12]. Recently, a wealth of previous studies have reported that microRNAs (miRNAs), a class of noncoding RNAs characterized by approximately 22 nucleotides in length, can inhibit the stability and translation of messenger RNAs (mRNAs) through binding to the specific sequence of genes, which are used as potential biomarkers for different kinds of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Culture-independent techniques using molecular methods with recombinant DNA have endowed researchers with tools for recognizing the organisms that reside in microbial communities, reducing the potentially misleading results arising from the vagaries of cultivation. With the advent of next-generation sequencing, studies have focused on a more holistic approach for the characterization and identification of microbial communities and their possible involvement in various diseases, including different types of cancer [11][12][13] Microbial dysbiosis can be defined as any change to the composition of resident commensal communities, relative to the community found in healthy individuals [14]. To date, very few studies have tried to address bacterial dysbiosis associated with oral/oropharyngeal cancers employing culture-independent approaches.…”
mentioning
confidence: 99%